2021
DOI: 10.1186/s12870-021-03189-x
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations in the leaf lipidome of Brassica carinata under high-temperature stress

Abstract: Background Brassica carinata (A) Braun has recently gained increased attention across the world as a sustainable biofuel crop. B. carinata is grown as a summer crop in many regions where high temperature is a significant stress during the growing season. However, little research has been conducted to understand the mechanisms through which this crop responds to high temperatures. Understanding traits that improve the high-temperature adaption of this crop is essential for developing heat-tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 70 publications
2
13
0
Order By: Relevance
“…A decrease in unsaturation or increase in saturation of fatty acids in membrane lipids was known to help maintain appropriate membrane fluidity at high temperature [ 9 ]. Similar to our results, HT treatment in Brassica carinata resulted in remodelling of leaf lipidome manifested by decreases in unsaturated levels of membrane lipids, especially C18:3, and increases in saturated fatty acids such as C16:0 [ 29 ]. These authors proposed that plants can modulate the level of unsaturation of membrane lipids by decreasing the activity of FAD3, FAD7 and FAD8, which catalyse the formation of C18:3, or by increasing the activity of FAD2 and fatty acid synthase (FAS), which catalyse the formation of C18:2 or C16:0, respectively.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A decrease in unsaturation or increase in saturation of fatty acids in membrane lipids was known to help maintain appropriate membrane fluidity at high temperature [ 9 ]. Similar to our results, HT treatment in Brassica carinata resulted in remodelling of leaf lipidome manifested by decreases in unsaturated levels of membrane lipids, especially C18:3, and increases in saturated fatty acids such as C16:0 [ 29 ]. These authors proposed that plants can modulate the level of unsaturation of membrane lipids by decreasing the activity of FAD3, FAD7 and FAD8, which catalyse the formation of C18:3, or by increasing the activity of FAD2 and fatty acid synthase (FAS), which catalyse the formation of C18:2 or C16:0, respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Brassica carinata cv. Avanza 641 responded to HT by decreasing the level of unsaturation in membrane lipid, especially in unsaturated linolenic acid (18:3) to maintain optimal membrane fluidity [ 29 ]. Moreover, soybean [ 30 ] and peanut [ 31 ] also responded to HT by decreasing lipid unsaturation levels to maintain membrane fluidity, and the magnitudes of reduction were greater for heat-tolerant than for heat-sensitive genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Data about such complex lipid alterations can be recorded with high-throughput mass-spectrometry-based analytical platforms. Several studies have employed MS-based lipidomics to profile changes in plant membrane lipids [ 4 , 5 , 7 , 8 , 9 , 10 ]. The ultimate goal of lipidomics is to determine the relative or absolute abundance of one, several, or all lipid species present in the sample [ 66 , 67 ].…”
Section: Mass Spectrometry-based Lipid Profilingmentioning
confidence: 99%
“…Lipid compositional variation in response to HT stress has been recorded in several plants such as Arabidopsis thaliana [ 6 ], wheat [ 7 , 8 ], soybean [ 9 ], and Ethiopian mustard ( Brassica carinata ) [ 10 ]. Djanaguiraman et al [ 7 ] have reported that in wheat, the decrease in photosynthetic rate under HT stress is due to thylakoid membrane damage, lipid composition alterations, and oxidative damage of organelles.…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified morpho-physiological traits enabling the selection of superior stress-tolerant genotypes at the early growth stage in rice ( Kakar et al, 2019 ; Reddy et al, 2021 ), corn ( Zea mays ) ( Wijewardana et al, 2015 ), sweet potato ( Ipomoea batatas ) ( Ramamoorthy et al, 2022 ), and cotton ( Brand et al, 2016 ). Likewise, variations in stress tolerance among carinata genotypes have been reported ( Angadi et al, 2000 ; Gesch et al, 2019 ; Zoong Lwe et al, 2021 ). There is limited information on carinata response to different temperature ranges during the early season.…”
Section: Introductionmentioning
confidence: 96%